PERLAWANAN PEREMPUAN DALAM NOVEL NAYLA KARYA DJENAR MAESA AYU (KAJIAN FEMINISME MARXIS) - Amanah Malik; Aslan Abidin; Suarni Suarni (Fakultas Teknik Universitas Negeri Makassar, 2023)
This study aims to analyze women's resistance in the novel Nayla, which is studied using the theory of Marxist feminism. This research is descriptive and qualitative in nature. The results of this study are as follows: it found the efforts of women apart from every problem that shackles them. The reasons behind women's attitudes to reject and even rebel against male power are caused by education, understanding of the law, and the people around them. Forms of women's resistance, namely, the existence of women's rights to control their own bodies, the existence of complete equality in the legal, political, and social fields for women, the existence of women's rights to economic independence and equality, the rights of women to be free from violence and sexual exploitation, and challenging the oppression of human sexuality.